2022
DOI: 10.1017/s0950268822001947
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the incubation period and generation time of SARS-CoV-2 Alpha and Delta variants from contact tracing data

Abstract: Quantitative information on epidemiological quantities such as the incubation period and generation time of SARS-CoV-2 variants is scarce. We analyzed a dataset collected during contact tracing activities in the province of Reggio Emilia, Italy, throughout 2021. We determined the distributions of the incubation period for the Alpha and Delta variants using information on negative PCR tests and the date of last exposure from 282 symptomatic cases. We estimated the distributions of the intrinsic generation time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Our estimate of the mean generation time (mean: 6.8 days) is compatible with previous estimates for ancestral lineages 18 (including a previous estimate for Italy of 6.7 days 19 ). Existing estimates for Alpha and Delta were in the same range in a study similar to the present one on the same study population in Italy (6.0 and 6.6 days respectively 15 ). We also found a mean household serial interval of 2.38 days, shorter than previous estimates for Delta of 2.56 on a similar study population.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our estimate of the mean generation time (mean: 6.8 days) is compatible with previous estimates for ancestral lineages 18 (including a previous estimate for Italy of 6.7 days 19 ). Existing estimates for Alpha and Delta were in the same range in a study similar to the present one on the same study population in Italy (6.0 and 6.6 days respectively 15 ). We also found a mean household serial interval of 2.38 days, shorter than previous estimates for Delta of 2.56 on a similar study population.…”
Section: Discussionsupporting
confidence: 86%
“…We also found a mean household serial interval of 2.38 days, shorter than previous estimates for Delta of 2.56 on a similar study population. 15 Available studies have suggested a shorter generation time of Omicron (between 50% and 80% the one of Delta) using population-level data on the growth rate of Omicron relative to Delta in Denmark 20 and United Kingdom. 21 An analysis of 43 infectorinfectee pairs from contact tracing data in Hong Kong 22 estimated a mean realized generation time of 2.38 days (95% confidence interval 2.01−2.80) under very strict control measures (population-wide screenings and quarantine imposed to both contacts and contacts of contacts) that are known to reduce the realized generation time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only a few studies have provided estimates of the incubation period, serial interval, and generation time of Delta variant infection. These studies suggest that the mean (or median) incubation period of Delta ranges from 3.0 to 6.0 days (3-4), which contains the mean estimate obtained in our study (5.3 days); also, our estimate of the serial interval (4.3 days) falls inside the range reported in previous studies (range 2.6-5.4 days) (5)(6). Regarding the generation time, we found only two studies providing estimates for Delta variant; the first one was conducted in the UK and found a mean value of 4.7 days (7), while the second one was † Contacts who were aged at or over 65 years or whose infectors were aged at or over 65 years were excluded from this analysis due to the small sample size.…”
Section: Sars-cov-2 Delta Variant Outbreak In Hunansupporting
confidence: 88%